2001
DOI: 10.1046/j.1365-2788.2001.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and young people with Down's syndrome: childhood predictors and adult outcome of disorder

Abstract: There is a scarcity of follow-up studies into adult life of psychiatric disorder in young people with intellectual disability. The key aims of the present study were: (1) to determine the outcome of psychopathology present in childhood in individuals with Down's syndrome (DS); and (2) to look at childhood predictors of adult psychiatric disorder. Fifty-two young people with DS were identified from a sample of 193 subjects examined in childhood and adolescence for psychiatric and behaviour disorder. These young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 18 publications
4
28
2
Order By: Relevance
“…The quality of the parent-child relationship is an important factor for adjustment into young adulthood among families with typically developing children (Overbeek, Stattin, Vermulst, Ha, & Engels, 2007). There is growing empirical support that family processes are also predictive of outcomes for individuals with intellectual and developmental disabilities across the life course (Esbensen, Mailick, & Silverman, in press; McCarthy & Boyd, 2001; Smith, Greenberg, Seltzer, & Hong, 2008). …”
Section: Positive Family Processesmentioning
confidence: 99%
“…The quality of the parent-child relationship is an important factor for adjustment into young adulthood among families with typically developing children (Overbeek, Stattin, Vermulst, Ha, & Engels, 2007). There is growing empirical support that family processes are also predictive of outcomes for individuals with intellectual and developmental disabilities across the life course (Esbensen, Mailick, & Silverman, in press; McCarthy & Boyd, 2001; Smith, Greenberg, Seltzer, & Hong, 2008). …”
Section: Positive Family Processesmentioning
confidence: 99%
“…Compulsive-like behaviour (including ritualistic habits and perfectionistic behaviours) was more frequent and conspicuous in children with Down syndrome compared with mental age-matched controls, suggesting that some repetitive behaviours may belong to the behavioural phenotype of individuals with Down syndrome (Evans & Gray, 2000). Childhood disorder in individuals with Down syndrome has a good early prognosis with little evidence of persistence into adult life (McCarthy & Boyd, 2001). Collacott et al (1992) compared adults with Down syndrome and adults with intellectual disabilities due to other aetiologies.…”
Section: Introductionmentioning
confidence: 99%
“…There is preliminary evidence that depression is relatively more common in DS subjects than in comparison to the ID population in general; this on a background of mental ill health (all causes) being less common in DS (Collacott et al, 1992;Mantry et al, 2008). It is also apparent that, excluding organic disorders such as dementia, depression is the most common psychiatric problem experienced (Myers and Pueschel, 1991;Mantry et al, 2008;Prasher, 1995;McCarthy and Boyd, 2001). The presentation of depression is likely to be varied, however, there is some evidence for the development of withdrawal symptoms and the possibility of psychosis.…”
Section: Resultsmentioning
confidence: 99%
“…Those with a disorder in adulthood showed no significant relationship with childhood scores of function. McCarthy and Boyd (2001) concluded that there was no evidence to suggest that childhood psychopathology predicts illness in adulthood. There was a suggestion that those with mixed conduct and emotional disorder may have an increased vulnerability to mood disorders in later life.…”
Section: Summary Of Studiesmentioning
confidence: 99%